“In-the-moment” feedback: A novel app for clinical teaching evaluations - Halani, Sheliza; Sujana Kumar, Shoba; Yin Lim, Dawn; Hefferon, Darren; Prakash, Varuna; Kumagai, Arno K; Bui, Esther (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementEncounter-based teaching is vital to medical education, however feedback can be difficult to obtain. We developed and evaluated a web-based application (app) called “myTeachingEvaluation” (myTE.orgTM). Thirty-four academic clinical teachers participated in a needs assessment; 47% reported ≥50% of their teaching was undocumented. We invited participants to pilot myTE.orgTM over eight weeks. Thirteen faculty piloted the app and 62% of them (8/13) reported the app enabled documentation of ≥50% of previously undocumented teaching. myTE.orgTM app creates opportunities for efficient and timely feedback.